PENGEMBANGAN BAHAN AJAR FISIKA BERBASIS SCIENTIFIC APPROACH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI MEDAN MAGNET DI SMA - Kurnia Mas Rahmawati; Sri Handono Budi Prastowo; Singgih Bektiarso (JURNAL PEMBELAJARAN FISIKA, 2019)
AbstractThis research aimed to produce scientific approach-based physics learning material in magnetic field topic, describe it’s validity, practicality, and effectiveness to improve students’ critical thinking skill. The development procedures of the research employed Nieveen’s research design which consisted of three stages, namely preliminary research, prototyping stage, and assessement stage. The instruments used in this research were validation sheet, observation sheet, and critical thinking test. Based on the results of the data analysis concluded: (1) the validity of scientific approach-based physics learning material was at very valid category with an average score of expert validation was 3.47 and average score of user validation was 3.67, (2) the practicality of scientific approach-based physics learning material was in very high category, (3) the effectiveness of scientific approach-based physics learning material to improve students’ critical thinking skill showed that the average of N-Gain score was 0.53 which was in the medium category, so the scientific approach-based physics learning material was effective in improving critical thinking skill.Key word: physics learning materials; scientific approach; magnetic field, critical thinking skill